Ultrafast processes in high temperature superconductors - Gay, P (2000)
Using time-resolved photo-induced reflectivity, we reported for the first time a systematic work on the ultrafast response of Bi2Sr2CaCu2O8+δ (BSCCO-2212) and Tl2Ba2CuO6+δ (TBCO-2201), measurements of detwinned YBa2Cu3O7-δ (YBCO-123) single crystal with the electric field ̲E parallel to the a and b-axis and high-resolution measurements of the rising edge dynamics of YBCO-123 thin films. We identified similar photo-induced responses for BSCCO, TBCO and for YBCO with ̲E ⊥ ̲b, which indicates that we observed a universal response of HTSC coming from the CuO2 superconducting planes. This latter dynamics is composed of three different components corresponding to the superconducting, pseudogap and normal state. A bi-molecular model has been put forward to explain the linear temperature dependence of the decay rate; the model implies that the re-formation of the condensate is limited by the rate at which quasiparticle interact. Moreover, we observed superconducting fluctuations up to 13K above Tc and a divergence of the long-lived component magnitude at very low temperature, which is explained by a cw heating model. In the pseudogap state, we have several indications that the negative peak observed between Tc and T* has a different origin from that of the superconducting signal below Tc. We argued that the probe mechanism of the pseudogap signal is electronic excitations of the pseudogap correlations. In the normal state, the observed dynamics is similar to that of simple metals. In the second part of this thesis, the rising edge dynamics of YBCO has been resolved in time. The model developed to interpret the results implies that the hot quasiparticles relaxation time down to the Fermi energy is 55fs. In this context, we proved that the Mazin model cannot explain both the oscillatory and the non-oscillatory part of the dynamics in YBCO. Finally, in YBCO-123, a new response has been observed with ̲E ∥ ̲b. We argued that the origin of this component is intraband transitions. This dynamics is solely responsive to the pseudogap, coming from the difference in scattering rate between pre-formed pairs and quasiparticles in the Drude reflectivity. The response with ̲E ⊥ ̲b exhibits a strong a-b plane anisotropy in its long-lived component, which can be interpreted as a d-wave gap symmetry using the thermally-activated model.